Análisis de los biomarcadores de monitorización del tratamiento en el Síndrome Nefrótico. - Chadán Yunapanta, Lissette Morayma (2024)
Nephrotic syndrome is a nephropathy characterized by alterations at the glomerular level that result in the development of an inflammatory process, leading to the presence of proteinuria > 3.5 g/day in adults and 40 mg/m2 in children. , hypoalbuminemia <3.5 g/dl, subsequently the development of edema, hyperlipidemia and hypercoagulability is evident. On the other hand, currently the use of corticosteroids in the treatment of nephrotic syndrome is common. However, given that almost half of patients with nephrotic syndrome present or subsequently develop corticosteroid resistance, it is vitally important to monitor patients during treatment with corticosteroids. To do this, biomarkers such as proteinuria, albuminemia and creatinine are used that contribute to the diagnosis and monitoring of the treatment of this pathology. However, reliable biomarkers have currently been identified in terms of sensitivity and specificity such Haptoglobin, Adiponectin (ADIPQ), Vitamin D binding protein (VDBP), Soluble urokinase-type plasminogen activator receptor (SuPAR), Hemopexin (HPX), Sex hormone binding globulin (SHBG) and Metalloproteinase-2 (MMP2), which allow determining the presence of corticosteroid resistance. Therefore, the objective of this study was to carry out a bibliographic review that provides evidence on the usefulness of biomarkers for monitoring the treatment of nephrotic syndrome. To search for information, a qualitative, descriptive, retrospective and documentary research was carried out, using bibliographic material with a maximum age of 5 years, located in different medical databases such as Scopus, UpToDate, Scielo, Science Direct, Cochrane. Library, PubMed among others. A total of 75 articles were obtained and after selecting the most appropriate ones using inclusion and exclusion criteria, the number was reduced to a final sample of 23 studies. Through this bibliographic review, it is concluded that the use of predictive biomarkers of steroid resistance makes it possible to identify patients in whom this therapy will have favorable results to counteract the disease.